Strategi Komunikasi Publik Melalui Konten Video Media Sosial pada Divisi Broadcasting Diskominfo Kota Bogor untuk Penyebaran Informasi - Sherly Puja Tania; Wahyu Budi Priatna (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study examines the public communication strategy implemented by the broadcasting division of the Bogor City Communication and Informatics Office (Diskominfo) in producing and disseminating video content through social media as a means of public information and education. A descriptive qualitative approach was used, using observation, interviews, and document study techniques to gain an in-depth understanding of contextual communication practices. The results indicate that the public communication strategy was implemented through three main stages: pre-production, production, and post-production. In the pre-production stage, messages relevant to community needs were planned. The production stage focused on creating content that was informative, engaging, and easily understood by the audience, while the post-production stage included the dissemination and evaluation of message effectiveness. Challenges encountered included limited resources, technical issues, and sometimes suboptimal coordination between departments. However, these obstacles were overcome through teamwork, technical training, and more efficient equipment management. This study confirms that video content plays a strategic role in strengthening the relationship between the government and the community and encouraging transparency and public participation. Continuous evaluation based on audience feedback is recommended to improve the effectiveness of future communication.